Intestinal Helminth Infections Among Primary School Pupils in Nimo Community, Njikoka Local Government Area, Anambra State, Southeastern Nigeria - A. E. , Onyido; M. M., Okoye; K. C., Irikannu; E. N., Okafor; C. N., Ugha; P. U. , Umeanaeto; C. M., Egbuche; M. O., Iwueze; A. C., Ezeani (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Study to determine the prevalence of intestinal helminth infections among primary schoolchildren in Nimo Community, Njikoka Local Government Area, Anambra State, Nigeria was undertaken.Four Primary Schools, namely Ugwu-Oye Primary School, Unity Primary School, St. Joseph’s PrimarySchool and Egbengwu Primary School were involved in the study. 120 pupils were selected from theschools and enlisted into the study. Direct smear and zinc sulphate solution (Flotation method) were usedfor the isolation of the helminth eggs. Of the 120 stool samples examined, 26(21.7%) harboured intestinal helminths, Egbengwu Primary School had the highest number of infection 10(33.3%) and St. Joseph’sPrimary School had the lowest 3(10.0%). Intestinal helminth infections observed were hookworms13(10.8%), Ascaris lumbricoides 7(5.83%), Trichuris trichiura 2(1.66%), Schistosoma mansoni 2 (1.66%), Strongyloides stercoralis 1(0.83%) and Taenia spp 1(0.83%). More females 14(23.3%) than the males12(20.0%) were infected. The age specific prevalence in the four schools was highest in 13-16 years agegroup 3(60.0%) and least in 5-8 years age group 8(16.0%). Government schools had higher prevalence of infection 18(30.0%) than private schools 8(13.3%). Generally poor sanitation, socio-economic status andignorance of the epidemiology of infection were related to the prevalence of infection.